Proses Produksi Highlight Pada Channel Youtube Cita Entertaiment - Rizky Nigtiaz; Ainur Rofiq (An-Nashiha: Journal of Broadcasting and Islamic Comunication Studies, 2023)
Cita Entertainment is a YouTube channel that produces entertainment content. One of the products that Cita Entertainment produces is video highlights, which are excerpts from television shows or other events presented in a more concise and attractive format. The highlight production process at Cita Entertainment begins with selecting the program to be highlighted. After that, the production team will watch the program and record important moments that will be used as highlights. They will also choose the right music to accompany the video. Once the key moments have been selected, the production team will start editing the video. They would cut out the unimportant parts and arrange the important moments chronologically. They will also add pre-selected visual effects and music. After the editing process is complete, the video will be reviewed and displayed if needed. Later, highlight videos will be uploaded to Cita Entertainment's YouTube channel and uploaded via social media or other platforms. In the production of highlights at Cita Entertainment, the production team always strives to produce videos that are interesting and entertaining, and meet high quality standards.